Features of the Widespread Involvement of Introduction of Information and Communication Technologies in the Tax Administration of Developed Countries - Ergashev Ikrom Abdurasulovich (Scientific Trends, 2024)
In this article, the author analyzes in detail features of the widespread involvement of introduction of information and communication technologies in the tax administration of developed countries. As a result of the analysis, the author made relevant conclusions and recommendations.
Keywords: Types of taxes, tax reform, tax concept, tax administration, tax and mandatory payments, tax system, tax policy, state tax departments, tax rate, single tax payments.